(Dis)graceful dancing bodies in South Africa. Issue 1 (1st April 2015) - Samuel, Gerard M.
Why is the inclusion of the disabled significant for Dance? How do the different ways in which dance by people with disabilities and older dancers aid one's understanding of Othering? This article extends my earlier discussion offered in 2008, 2009, 2010, 2011a, 2011b and 2012 that these largely marginalized groups suffer similar fate of invisibility within concert/theatre dance in South Africa. Gayatri Spivak's provocation of the voiceless and Sylvia Glasser's politics of dance foreground my argument of diverse dancing bodies. Dance, like multiple Englishes, opens up avenues of tolerance and grace for all South Africans. Recent choreographic examples such as Ina Wichterich-Mogane's Lovaffair and Ananda Fuchs's Fragile Falling reflect a continuum of disgraceful dancing bodies, marked on the periphery that could be seen as an aesthetic and ethical necessity in postcolonial spaces. These inclusions could constitute new pathways to valuing the lived and performative experiences of such diverse bodies.